The orbitofrontal cortex - Zald, David H.; Rauch, Scott L. (Oxford : Oxford University Press, 2006)
The orbitofronal cortex plays a critical role in emotion, learning, and behavioural flexibility. This volume provides a reference for established clinicians and researchers as well as trainees in neurology, neurosurgery, psychiatry, psychology, and neuroscience.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Frontal lobes